Analisis Budaya Organisasi dan Lingkungan Kerja Terhadap Organizational Citizenship Behavior (OCB) - Fattah Ario Wibowo (SMARTINDO, 2022)
Purpose of this article: This study aims to test the effect of organizational culture to OCB and workenvironment to OCB.Methodology: Research methodology is quantitative methodology and analyzed by descriptive and regression analysis to test the relation between variables. Results: Organizational culture and work environment has a significant effect to OCB, so it is more profitable for the company